Longitudinal evaluation of T-cell responses to Pfizer-BioNTech and Janssen SARS-CoV-2 vaccines as boosters in Ghanaian adults - Osei, Frank; Tudzi, Kekeli Korshi; Othol, Isaac Otieno; Segbefia, Selorm Philip; Prah, Diana Ahu; Armah-Vedjesu, Evans Nii; Pobee, Abigail Naa Adjorkor; Darko, Oscar Nii Otto; Brenko, Theophilus; Teye-Adjei, Doreen; Nartey, Stella; Amponsah, Jones Amo; et al. (Frontiers in Immunology, 2025)
IntroductionIn Ghana, at least five different COVID-19 vaccines based on mRNA or adenovirus vector delivery platforms have been authorized by the Ghana Health Service for vaccination. Although these vaccines have been instrumental in the control of COVID-19, data on the longevity of induced immunity in vaccinated individuals in Ghana is limited. This study aimed at assessing the cellular immune response kinetics among Ghanaians receiving booster vaccinations with the mRNA-based Pfizer and adenovirus-based Janssen COVID-19 vaccines.MethodsWe conducted a longitudinal study using 48 Ghanaian adults who had completed primary vaccination series and administered a booster shot with either of the two vaccines. Pre-booster blood samples were collected to serve as the baseline, and post-booster samples at months 3, 6, and 9 for immunological analysis. T-cell responses were assessed using Luminex multiplex assay following stimulation of Peripheral Blood Mononuclear Cells (PBMCs) from study participants with SARS-CoV-2 antigens, whereas immune checkpoint molecules expression was assessed by flow cytometry.ResultsAppreciable levels of the Th1 cytokines IL-1β, IL-6, IFN-γ and TNF-α and low levels of IL-2, IL-12 and IL-17A were observed in both groups. The Janssen vaccine booster elicited a more sustained cellular response over the nine months, while the Pfizer vaccine booster group showed signs of response decline after three months. Further sub-analysis showed that persons who received an mRNA-based primary vaccination before a viral vector vaccine booster had more durable cytokine responses. Checkpoint molecules, PD-1, CTLA-4 and TIM-3 were expressed at low levels (<10% of CD4+ or CD8+ T cell population with p-values > 0.05) and comparable between the two groups over the nine months.Discussion/conclusionsLevels of some cytokines were generally more sustained in the Janssen group compared to the Pfizer group. Heterologous vaccine recipients exhibited more efficient cellular immune responses compared to homologous recipients. In addition, T-cell inhibitory molecule kinetics suggests an efficient T-cell activity. These findings may have implications for the overall induction of long-term protective immunity by the two vaccine types.